Dynamics of Money Politics, and Generation Z's Political Choices in the 2024 Regional Elections in Sidoarjo Regency - Muhammad Julian Fitranta; Abd Rohman (PT Pro Panoramic Solution, 2025)
The phenomenon of money politics remains a significant issue in the context of electoral politics, particularly ahead of the 2024 Regional Elections in Sidoarjo Regency. This study aims to analyze the relationship between the dynamics of money and political practices and the political choices of Generation Z, which has unique characteristics as a digital and critical generation. Using qualitative approaches and voter behavior theory as the framework of analysis, research data were obtained through in-depth interviews, literature studies, and field observations. The results of the study show that although Generation Z in Sidoarjo Regency tends to be critical of the practice of money politics, the influence of economic incentives is still a factor that influences some of them in making political choices. In addition, social media was found to have an important role in shaping Generation Z's political opinions, both for and against money politics. In conclusion, money politics remains a significant challenge in local democracy, although Generation Z shows potential as more conscious agents of political change. This study recommends strengthening political education and regulation to minimize the negative impact of money politics in upcoming elections.